Ligation of Soluble but Unreactive Peptide Segments in the Chemical Synthesis of Haemophilus Influenzae DNA Ligase. Issue 35 (25th July 2019) - Zhang, Baochang; Deng, Qiang; Zuo, Chong; Yan, Bingjia; Zuo, Chao; Cao, Xiu‐Xiu; Zhu, Ting F.; Zheng, Ji‐Shen; Liu, Lei
Abstract: During the total chemical synthesis of the water‐soluble globular Haemophilus Influenzae DNA ligase (Hin‐Lig), we observed the surprising phenomenon of a soluble peptide segment that failed to undergo native chemical ligation. Based on dynamic light scattering and transmission electron microscopy experiments, we determined that the peptide formed soluble colloidal particles in a homogeneous solution containing 6 m guanidine hydrochloride. Conventional peptide performance‐improving strategies, such as installation of a terminal/side‐chain Arg tag or O ‐acyl isopeptide, failed to enable the reaction, presumably because of their inability to disrupt the formation of soluble colloidal particles. However, a removable backbone modification strategy recently developed for the synthesis of membrane proteins did disrupt the formation of the colloids, and the desired ligation of this soluble but unreactive system was eventually accomplished. This work demonstrates that an appropriate solution dispersion state, in addition to good peptide solubility, is a prerequisite for successful peptide ligation. Abstract : The surprising phenomenon of a soluble peptide segment that failed to undergo native chemical ligation was observed and attributed to the formation of soluble colloidal particles in an aqueous guanidine hydrochloride (6 m ) solution (A). A removable backbone modification strategy (B) was found to be effective for achieving the ligation of this soluble but unreactive system.